theresia KEANEKARAGAMAN SPESIES DAN STATUS KONSERVASI HIU (Elasmobranch) DI TARAKAN: IMPLIKASI UNTUK PENGELOLAAN BERKELANJUTAN BERBASIS BLUE ECONOMY - theresia Theresia; Denny Indrawanto; M. Gandri Haryono; Muhammad Muhammad Firdaus; Leo Oscar (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
Global shark populations have declined drastically due to intense fishing pressure, including in Tarakan, North Kalimantan—a key landing area with limited data on species diversity and conservation status. This issue is exacerbated by the use of non-selective fishing gear such as mini trawls, which result in significant shark bycatch. This study aims to identify shark species caught as bycatch and assess their conservation status. Data were collected from March to May 2025 through field observation and morphological identification. Five shark species were recorded: Chiloscyllium plagiosum, Chiloscyllium punctatum, Hemigaleus microstoma, Sphyrna lewini, and Rhynchobatus austraiae, totaling 145 individuals. The Shannon-Wiener diversity index (H' = 1.35) indicates moderate diversity, with S. lewini being the most dominant. According to the IUCN Red List, two species are Critically Endangered (CR), one Vulnerable (VU), one Near Threatened (NT), and one Least Concern (LC). These findings highlight Tarakan waters as a critical habitat for threatened shark species and emphasize the urgent need for sustainable fisheries management based on blue economy principles, including bycatch reduction, fisher education, and development of conservation-based economic alternatives. Keywords: sharks, bycatch, conservation status, Tarakan, blue economy